The Importance of Sleep in Athletic Performance - A Systematic Review - Białeta, Julia; Rowińska, Katarzyna; Siembab, Karolina; Jurkiewicz , Michalina; Napieralska, Agnieszka; Garbarczyk, Wiktor; Kapla, Albert; Černohorská, Alicja; Pysiewicz, Wiktoria; Bednarczyk, Daria (Quality in Sport, 2025)
Introduction Sleep influences the well-being of every person, but it is especially important for athletes1. This review analyses the impact that quality and duration of sleep has on physical and cognitive performance in athletes. It also examines the strategies for optimizing sleep, such as extending the duration of sleep, adding naps during the day and educating athletes about sleep hygiene. Results Research conclusively states that insufficient sleep impairs physical endurance and strength, reduces coordination and increases injury risk2–5. It impacts cognitive processes – decreases focus, diminishes strategic thinking and slows reaction times6. Evidence reveals that sleep interventions such as prolonging sleep duration, napping during the day and blue-enriched light exposure lead to improving sleep in athletes7. Summary By integrating findings from a range of studies, this review emphasizes the role of sleep as an indispensable pillar of sports performance optimization. It offers practical implications and limitations to the analyzed studies.